Analysis of Science Process Skills:The Impact of Project-Based Learning Assisted by Mind Mapping on Biology Subjects - Puspita, Laila; Hidayah, Nur; Indrawan, Ahmad Rafi; Komarudin, Komarudin; Carolina, Hifni Septina (Biosfer: Jurnal Tadris Biologi, 2024)
This study aims to determine the influence of the Project-Based Learning model assisted by Mind Mapping on Science Process Skills in the field of biology. The research method used is a Quasi-Experimental design with a Pretest-Posttest Control Group Design. The population for this study consisted of grade XI students and sampling techniques by means of random sampling techniques. The data collection techniques used in the instrument include multiple-choice questions to assess Science Process Skills and then test the validity, reliability, level of difficulty, and discriminatory power so that the instrument is suitable for use. The data analysis technique used was Analysis of Variance (ANOVA), and the results obtained showed a significance value of 0.000 < α = 0.05, indicating that H1 was accepted and H0 was rejected. Thus, it can be concluded that there is a significant influence of the use of the Project-Based Learning model assisted by Mind Mapping on the Science Process Skills of studentABSTRAK: Penelitian ini bertujuan untuk mengetahui pengaruh Model Pembelajaran Project Based Learning berbantu Mind Mapping terhadap keterampilan proses sains peserta didik pada mata pelajaran biologi. Metode penelitian yang digunakan yaitu Quasy Experimental dengan desain penelitian Pretest-Posttest Control Group Design. Populasi penelitian ini yaitu peserta didik kelas XI. Teknik pengumpulan data menggunakan instrumen berupa soal tes Multiple Choice Keterampilan Proses Sains yang telah dilakukan uji validitas, reliabilitas, tingkat kesukaran, dan daya pembeda, sehingga instrumen layak digunakan. Teknik analisis data yang digunakan yaitu uji Analysis of varians (Anova), dan didapatkan hasil yang menunjukkan bahwa nilai signifikansi sebesar 0,000 < α=0,05, dengan ketentuan H1 diterima dan H0 ditolak. Sehingga, dapat disimpulkan bahwa terdapat pengaruh yang signifikan penggunaan model pembelajaran Project Based Learning berbantu Mind Mapping terhadap Keterampilan Proses Sains peserta didik.